151k views
1 vote
SoMeonE plZ hAlp me lol

SoMeonE plZ hAlp me lol-example-1

1 Answer

1 vote

So we can solve this using the Pythagorean theorem. The basic equation is as follows:



a^(2) +b^(2)= c^(2)


where a and b are the values of the two legs of a right triangle, and c is the value of the hypotenuse.


So let's plug in the values given via the picture:



14^(2)+ x^(2)= 17^(2)


And then we solve for x:



196+x^(2) =289



x^(2) =93



x=√(93)


So now we know the value of x is the squareroot of 93.

User Romtsn
by
5.0k points